THE INFLUENCE OF RELIGIOSITY AND UNDERSTANDING OF MANUFACTURERS ON COMPLIANCE WITH HALAL LABELING CERTIFICATION IN KEC. LENGAYANG, PESISIR SELATAN - AULIYAH, RAHMINA; WAHYUDIN, RAMA; PUTRA, GUSTI DIRGA ALFAKHRI (Maqdis: Jurnal Kajian Ekonomi Islam, 2024)
The inclusion of halal label certification on food makes it an effective means for consumers to sort halal food more easily and is a form of producer responsibility in doing business and protecting consumers. However, consumers have the right to know and obtain clear and detailed information regarding every composition or material used in the manufacture of products that have been traded. This is also because the products circulating in the community are not necessarily safe, especially for Muslim consumers. This study aims to examine the effect of religiosity and producer understanding of halal labeling certification on food products. The data used are primary data and secondary data. Variable testing was carried out using the classical assumption test, multiple linear regression analysis statistical tests through the SPSS 16 program analysis.